Gambaran Karakteristik Pengetahuan Ibu yang Memiliki Balita dengan ISPA di Puskesmas Siliwangi Garut - Sandra Pebrianti; Iwan Shalahuddin (STIKes Karsa Husada Garut, 2018)
ISPA (Upper Respiratory Tract Infection) is a health problem that often occurs in the community especially in infants, toddlers and children, this is a reflection for all of us that to realize a high degree of health is not easy. Infection of the acute respiratory tract. Knowledge is the result of knowing and this happens after someone has sensed a certain object. Sensing occurs through the five human senses, namely the senses of sight, smell, taste, touch, and taste. Most human knowledge is obtained through the eyes and ears. Objective To find out